UNIT 4.67 Solid‐Phase Synthesis of DNA and RNA 5′‐O‐Triphosphates Using cycloSal Chemistry. Issue 1 (1st March 2016) - Sarac, Ivo; Meier, Chris
Abstract : A chemical method for the synthesis of short strands of DNA and RNA 5′‐ O ‐triphosphates is described that makes use of the conventional coupling and oxidizing reagents that are readily available on standard DNA/RNA synthesizers. After automated solid‐phase synthesis of oligonucleotides and 5′‐ O ‐detritylation, a novel cyclo Sal‐phosphoramidite, 5‐chloro‐saligenyl‐ N, N ‐diisopropylphosphoramidite, was coupled to the 5′‐hydroxyl group and the product oxidized. The resulting support‐bonded 5′‐ cyclo Sal‐oligonucleotide was reacted with pyrophosphate to yield 5′‐ O ‐triphosphorylated DNA/RNA oligonucleotides after cleavage from the support in high purity and excellent yields. The reaction sequence was adapted to be used completely on a standard automated oligonucleotide synthesizer. © 2016 by John Wiley & Sons, Inc.